Optimization of Pre-treatment Conditions for Direct PCR Analysis of Human Bloodstains at Various Storage Durations (Journal of Forensic Medicine & Toxicology, 2026)
The polymerase chain reaction (PCR) has undergone significant advancements and has been applied in various fields,  including forensics. In the field of forensic analysis, rapidity and efficiency are paramount. One promising technique  is direct PCR, which involves conducting PCR analysis without DNA extraction, facilitating a more rapid and efficient  analysis. However, treating samples used directly as templates is essential to ensure the PCR reaction can proceed. This  study involved optimizing the treatment of blood samples (incubation at 60°C and 90°C for 10 minutes) prior to their  use as a direct PCR template and evaluating the effectiveness of direct PCR on human bloodstains incubated for various  durations (0, 7, 14, 21, and 30 days) using primers of the human cytochrome b gene. The gene has significant variation  between species, but limited variation within the species. The results indicated that the cytochrome b gene primers suc cessfully amplified human DNA. Samples incubated at 90°C for 10 minutes or at 60°C for 10 minutes could be used as  direct PCR templates. Human bloodstains remained analyzable using direct PCR up to 30 days following the initial sampling. This study provides valuable insights for forensic experts, enabling them to expedite and enhance the efficiency of  the PCR process in forensic applications.
Keywords: DNA; Direct PCR; Crime; Cytochrome b; Blood